Ambipolar Plasmon‐Enhanced Photodetector Built on Germanium Nanodots Array/Graphene Hybrid. Issue 20 (26th August 2020) - Gao, Min; Tian, Ziao; Tang, Shiwei; Han, Xiaowen; Zhang, Miao; Xue, Zhongying; Zhu, Wei; Mei, Yongfeng; Chu, Paul K.; Wang, Gang; Di, Zengfeng
Abstract: Graphene with gate‐tunable electronic properties is promising as the channel materials in ambipolar multifunctional photodetectors. However, owing to the zero bandgap and weak light absorption, photodetectors fabricated on pristine graphene have low photoresponsivity. Herein, an ambipolar multifunctional photodetector with improved photocurrent and response speed is constructed on germanium (Ge) nanodots array‐decorated graphene. The photocurrent map and simulated electric field distributions reveal that the enhanced photo‐response is attributed to the localized surface plasmonic resonance effects by trapping light around the Ge nanodots. The photodetector exhibits ambipolar photo‐response and the photocurrents can be tuned from negative to positive by applying different gate voltages due to the gate‐tunable Fermi level of graphene. This ambipolar photodetector with fast response has excellent potential in imaging and sensing arrays as well as multifunctional photodetectors. Abstract : An ambipolar multifunctional photodetector with improved photocurrent and response speed is constructed on germanium nanodots array‐decorated graphene. Owing to the localized surface plasmonic resonance, light scattered by an individual nanodot can be collected by neighboring nanodots to increase the photocurrent and shorten the response time. Besides, the photocurrents can be tuned from negative to positive by applying different gate voltages.